Analyzing Children’s Trauma during the Covid-19 Pandemic Using Relational-Cultural Theory: A Literature Review - Dewanti, Septinda Rima; Wu, Yuejiao (Jurnal Kajian Bimbingan dan Konseling, 2023)
The impact of the Covid-19 pandemic has been extensively discussed, but only a limited number of studies investigate how pandemics are related to traumatic experiences for children. Using a literature review of 38 peer-reviewed articles, both qualitative and quantitative published in the reputable international journals, this study examines how pandemic situations trigger trauma in children. From the literature review, we concluded a number of impacts of Covid 19 on children, including their experience of sudden and shocking changes of events, loss, grief, domestic violence, Covid-19 infections, being surrounded by an adult experiencing mental health disturbance, and becoming the victim of financial restraint faced by their parents. In the frame of relational-cultural theory, parents, caretakers, and educators must help children to reconnect with their peers and environment to face adverse experiences caused by the covid-19 pandemic by providing mutual empathy and building trustworthiness. As culture is an active factor in relational processes, we need to consider individual cultural values to support children who have experienced trauma during the pandemic.